PEMANFAATAN TUMBUHAN UNTUK BEBERAPA UPACARA ADAT OLEH MASYARAKAT DESA PANGANDARAN KECAMATAN PANGANDARAN KABUPATEN PANGANDARAN - Asep Zainal Mutaqin; Windi Astriani; Teguh Husodo; Ruhyat Partasasmita (Jurnal Pro-Life, 2018)
The study was conducted to determine the types of plants that are used in some traditional ceremonies are still carried out by the community in the Pangandaran Village, Pangandaran sub district, Pangandaran District . The research method used a qualitative method. Techniques of data retrieval is done by semi structured interview. The selection of informants was done by snowball sampling . The results showed there are several types of ceremonies are still performed by villagers in Pangandaran like the intent of the sea, four months, seven months, marriage, and the intent of the earth ceremony. Plants used in traditional ceremonies consist of 21 species, i.e. banana (Musa acuminate x balbisiana), banana (Musa paradisiaca) var. Sapientum (L.) Kunt, golden banana (Musa acuminata), coconut (Cocos nucifera L.), red roses (Rosa hybrida), white roses (Rosa hybrida), jasmine (Jasminum sambac Ait.), magnolia (Michelia champaca L.), ylang flower (Canangium odoratum Baill.), tuberose (Epiphyllum oxipetalum), bamboo (Bambusa vulgaris Schrad. Ex. Wndl. var vulgaris), a paper flower (Bougainvillea spectabilis Willd.), yam (Pachyrhizus erosus Urban.), rose apple (Eugenia aquea Burm. f.), papaya (Carica papaya L.), cassava (Manihot esculenta Crantz.), ambarella (Spondias pinnata Kurtz.), sweet potato (Ipomoea batatas Lamk.), taro (Xanthosoma sagittifolium (L.) Schott.), canna (Canna edulis Ker.), and rice (Oryza sativa L.). Plants are obtained by people from around the grounds, gardens, paddy, and some are bought in the market.Keywords: Pangandaran, Plant, Traditional Ceremony